Investigation of well testing reservoirs with multiphase flow in a mature field. (February 2021) - Xu, Wenbin; Liu, Ronghe; Yang, Haiyuan; Zhang, Li; Yang, Yongfei
When oil fields reach the high water-cut stage or in late development, the multiphase flow of oil/gas or oil/water, even oil/gas/water will occur in a reservoir. The conventional well test approaches are no longer applicable to this situation. Many studies have been done on multiphase well testing, including traditional multiphase flow well testing and numerical well testing approaches. In focusing on traditional multiphase flow well testing approaches, this work builds a 3D model using Eclipse software to examine the pressure response on a well located in the center of an anticline reservoir with a closed system. The results show that the Perrine-Martin (P-M) approach is the simplest one and is suitable for all reservoir systems. While the pressure-squared approach is only suitable for low rate conditions in an oil–water system. Pseudo-pressures are complicated and can only be used in a gas–oil system.